Distribution of Industrial Farms in the United States and Socioeconomic, Health, and Environmental Characteristics of Counties. (13th August 2013) - Harun, S. M. Rafael; Ogneva-Himmelberger, Yelena
Abstract : The method of producing food animals has changed in the United States over the past century, moving from traditional burns to enclosed structures resembling industrial buildings, where animals are raised in high stocking density (commonly known as "Concentrated Animal Feeding Operations, " CAFOs). The objective to maximize profit has resulted in poor farm management; raised issues of environmental pollution, public health, animal rights, and environmental justice, and had socio-economic impacts. Studies concerning the issues are limited to specific regions and types of CAFOs. In addition, studies on the spatial distribution and temporal changes of CAFO at a country scale are lacking. This study bridges some of the gaps by analyzing the spatial distribution of industrial farms in the United States in 2002 and 2007 and their relationship with vulnerable population and exploring the relationships among the concentrations of farms, socio-economic, health, and environmental characteristics of the counties. A range of spatial statistics tools were applied in this study. The study revealed variations in spatial distribution depending on the type of the CAFOs. The issue of environmental justice was found prevalent depending on the types of industrial farms. Each type of industrial farm was found to interact uniquely with the selected demographic, health, and environmental parameters.